2021
DOI: 10.33552/jtsft.2021.08.000686
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Antimicrobial Activity of Four Bangladeshi Medicinal Plants Used as Antimicrobial Finishes on Cotton Fabric

Abstract: Antimicrobial finish is an overwhelming area in the field of medical textile. It has significant technical and commercial applications in healthcare. The operation which is done to improve the appearance and usefulness of the textile fabric is generally known as textile finishing. Among two types of textile finishing, mechanical and chemical, antimicrobial finishing can be counted in chemical finishing. Antimicrobial finish can change fabric's several properties, for instance aesthetic properties, physical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Furthermore, physiological wearable sensors, such as heart-rate monitors, electrodermal activity sensors, skin-temperature sensors, eye trackers, and brainwave monitors, continuously monitor workers' activities and provide real-time feedback, effectively identifying high-risk activities and reducing occupational injuries [11]. Research efforts have been also focused on the development of safer personal protective equipment (PPE), clothing, and sustainable industrial solutions as key strategies for ensuring health, safety, and sustainability in various industrial environments [21,22]. While wearable sensors offer significant advantages in monitoring workers' safety and health, they also present challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, physiological wearable sensors, such as heart-rate monitors, electrodermal activity sensors, skin-temperature sensors, eye trackers, and brainwave monitors, continuously monitor workers' activities and provide real-time feedback, effectively identifying high-risk activities and reducing occupational injuries [11]. Research efforts have been also focused on the development of safer personal protective equipment (PPE), clothing, and sustainable industrial solutions as key strategies for ensuring health, safety, and sustainability in various industrial environments [21,22]. While wearable sensors offer significant advantages in monitoring workers' safety and health, they also present challenges.…”
Section: Introductionmentioning
confidence: 99%
“…There are two different antimicrobial treatments that are applied to textiles: synthetic antimicrobial finishes (both organic and inorganic), and natural antimicrobial finishes. Synthetic antimicrobial agents used are antimicrobial dyes, quaternary ammonium compounds, triclosan, metals and metal salts such as silver, zinc, and copper and natural agents are those that utilize a variety of components from the plant or animal kingdom [5]. Although synthetic antimicrobial agents are very effective against microbial growth on textiles these are caused by different side effects on consumers' health and water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Ashraf et al [5] reported a comparative idea for the application of antimicrobial finishes on bleached cotton fabric using plant leaf extract. Overall, the result indicates the potentiality of these plant extract to be used for anti-microbial textile product [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation